Zad.
Uzupełnij zapisy w taki sposób, aby w drugim równaniu występowała tylko jedna niewiadoma.
a).
{ x - 2y = 5
x + y = 26
{ x = ...
... + y = 26
b).
{2x + y = 7
5x - 2y = 4
{ y = ...
5x - ... = 4
c).
{ 3x + 4y = 8
9x - 7y = -14
{3x = ...
3 * (...) - 7y = - 14
d).
{ 5x + 2y = 7
3x - 6y = 5
{ 2y = ...
3x - ... * ( 7- 5x )= 5
e).
{ 2x = 6 - 4y
5x - 3y = 2
{ x = ...
... - 3y = 2
f).
{ 3y = 6x + 12
7x = 5y
{ y = ...
... = ...

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T08:43:23+01:00
A).
{ x - 2y = 5
x + y = 26
{ x = 5 + 2y
5 + 2y + y = 26



b).
{2x + y = 7
5x - 2y = 4
{ y = 7 - 2x
5x - (7 - 2x) = 4


c).
{ 3x + 4y = 8
9x - 7y = -14
{3x = 8 - 4y
3 * (8 - 4y) - 7y = - 14


d).
{ 5x + 2y = 7
3x - 6y = 5
{ 2y = 7 - 5x
3x - 3 * ( 7- 5x )= 5


e).
{ 2x = 6 - 4y
5x - 3y = 2
{ x = 3 - 2y
5 * (3 - 2y) - 3y = 2


f).
{ 3y = 6x + 12
7x = 5y
{ y = 2x + 4
7x = 5 * (2x + 4)
13 3 13
  • Roma
  • Community Manager
2010-02-14T08:49:05+01:00
A).
{ x - 2y = 5
{ x + y = 26

{ x = 5 + 2y
{ 5 + 2y + y = 26

b).
{ 2x + y = 7
{ 5x - 2y = 4

{ y = 7 - 2x
{ 5x - 7 + 2x = 4

c).
{ 3x + 4y = 8
{ 9x - 7y = -14

{ 3x = 8 - 4y
{ 3 * (8 - 4y) - 7y = - 14

d).
{ 5x + 2y = 7
{ 3x - 6y = 5

{ 2y = 7 - 5x
{ 3x - 3 * ( 7- 5x )= 5

e).
{ 2x = 6 - 4y
{ 5x - 3y = 2

{ x = 3 - 2y
{ 15 - 10y - 3y = 2

f).
{ 3y = 6x + 12
{ 7x = 5y

{ y = 2x + 4
{ 7x = 10x + 20
8 4 8